Depth, hard coral, and turf cover as predictors of micro-scale spatial distribution of fishes in a subtropical rocky reef - Rodrigues, Thiago E. (2024)
The combination of the physical structural heterogeneity of the environment, oceanographic characteristics, and the benthic assemblage composition structures the habitat, consequently shaping the associated diversity of fish. Understanding the spatial variability of fish assemblages and how it relates to environmental factors is essential to identify potential variables that determine spatial patterns and predict impacts on fish assemblage metrics, thus providing valuable information for management. Here, we investigated reef fish micro-scale spatial distribution around Alcatrazes Island in the subtropical region of the Southwest Atlantic, Brazil. Multivariate Regression Trees were fitted to explore the effects of structural heterogeneity, wave power, depth, water temperature, and benthic cover on the structure of reef fish assemblages, addressing composition, richness, density, biomass, trophic groups, mobility, and conservation status. Our results suggest that depth, turf, and coral cover were the main predictors of fish assemblages in rocky reefs at Alcatrazes Island, revealing five distinct fish assemblages with different habitat preferences. These results provide additional insights into the relationship between reef fishes and their environment, providing empirical evidence for decision-makers to implement spatially based management policies, especially to prioritize zones for conservation along the island.